Muscle Amino Acid and Adenine Nucleotide Metabolism during Exercise and in Liver Cirrhosis: Speculations on How to Reduce the Harmful Effects of Ammonia - Holeček, Milan (Metabolites, 2022)
Studies from the last decades indicate that increased levels of ammonia contribute to muscle wasting in critically ill patients. The aim of the article is to examine the effects of two different causes of hyperammonemia-increased ATP degradation in muscles during strenuous exercise and impaired ammonia detoxification to urea due to liver cirrhosis. During exercise, glycolysis, citric acid cycle (CAC) activity, and ATP synthesis in muscles increase. In cirrhosis, due to insulin resistance and mitochondrial dysfunction, glycolysis, CAC activity, and ATP synthesis in muscles are impaired. Both during exercise and in liver cirrhosis, there is increased ammonia detoxification to glutamine (Glu + NH3 + ATP → Gln + ADP + Pi), increased drain of ketoglutarate (α-KG) from CAC for glutamate synthesis by α-KG-linked aminotransferases, glutamate, aspartate, and α-KG deficiency, increased oxidation of branched-chain amino acids (BCAA; valine, leucine, and isoleucine), and protein-energy wasting in muscles. It is concluded that ammonia can contribute to muscle wasting regardless of the cause of its increased levels and that similar strategies can be designed to increase muscle performance in athletes and reduce muscle loss in patients with hyperammonemia. The pros and cons of glutamate, α-KG, aspartate, BCAA, and branched-chain keto acid supplementation are discussed.
Keywords: glutamic acid; branched-chain amino acids; glutamine; hyperammonemia